2001
DOI: 10.1074/jbc.m104547200
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Distribution of Lysosomal Sialidase Is Controlled by the Internalization Signal in Its Cytoplasmic Tail

Abstract: Sialidase (neuraminidase), encoded by the neu-1 gene in the major histocompatibility complex locus catalyzes the intralysosomal degradation of sialylated glycoconjugates. Inherited deficiency of sialidase results in sialidosis or galactosialidosis, both severe metabolic disorders associated with lysosomal storage of oligosaccharides and glycopeptides. Sialidase also plays an important role in cellular signaling and is specifically required for the production of cytokine interleukin-4 by activated T lymphocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 49 publications
(34 reference statements)
2
93
1
2
Order By: Relevance
“…6). Although the mechanisms through which NEU1 might be translocated to the plasma membrane are poorly understood, it has been detected on the surface of multiple cell types (47)(48)(49). A tyrosine-containing internalization motif in the COOH terminus of NEU1, amino acids 412-415, reportedly targets the enzyme to the lysosome in COS-7 cells, human skin fibroblasts, and lymphocytes (48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6). Although the mechanisms through which NEU1 might be translocated to the plasma membrane are poorly understood, it has been detected on the surface of multiple cell types (47)(48)(49). A tyrosine-containing internalization motif in the COOH terminus of NEU1, amino acids 412-415, reportedly targets the enzyme to the lysosome in COS-7 cells, human skin fibroblasts, and lymphocytes (48).…”
Section: Discussionmentioning
confidence: 99%
“…A tyrosine-containing internalization motif in the COOH terminus of NEU1, amino acids 412-415, reportedly targets the enzyme to the lysosome in COS-7 cells, human skin fibroblasts, and lymphocytes (48). Upon NEU1 Tyr-412 phosphorylation in activated lymphocytes, NEU1 is redistributed to the cell surface (48). In other studies, NEU1 was targeted to the plasma membrane of phorbol 12-myristate 13-acetate-differentiated human monocytes (47) and activated human T lymphocytes (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies revealed the presence of glycohydrolases not only in lysosomes but also at cell surface [5,18,39,40]. They stress the potential role of a remodelling of glycosphingolipids during cellular processes [6,7]. In a recent study we demonstrated that a mature form of hexosaminidase (Hex A isoenzyme) is associated to the human fibroblast PM and is catalytically active toward its natural substrate GM2 [26].…”
Section: Discussionmentioning
confidence: 97%
“…For instance, evidence for PM sialidase Neu3 activity towards gangliosides exposed to the surface of adjacent cells has been recently demonstrated by co-culture experiments [5,6]. Moreover, the presence of the lysosomal sialidase Neu1 anchored to both lysosomal and plasma membranes has been established and an important immunoregulatory role for this enzyme has been suggested [7,8]. In particular the translocation of sialidase Neu1 from lysosomes to PM has been observed during T-cell activation, where its ability to desialylate GM3 is required for IL-4 production in activated T-cells [9][10][11].…”
Section: Introductionmentioning
confidence: 96%